Agent based-stock flow consistent macroeconomics: Towards a benchmark model - Caiani, Alessandro; Godin, Antoine; Caverzasi, Eugenio; Gallegati, Mauro; Kinsella, Stephen; Stiglitz, Joseph E. (Journal of economic dynamics & control, 2016)
The paper moves from a discussion of the challenges posed by the crisis to standard macroeconomics and the solutions adopted within the DSGE community. Although several recent improvements have enhanced the realism of standard models, we argue that major drawbacks still undermine their reliability. In particular, DSGE models still fail to recognize the complex adaptive nature of economic systems, and the implications of money endogeneity. The paper argues that a coherent and exhaustive representation of the inter-linkages between the real and financial sides of the economy should be a pivotal feature of every macroeconomic model and proposes a macroeconomic framework based on the combination of the Agent Based and Stock Flow Consistent approaches. The papers aims at contributing to the nascent AB-SFC literature under two fundamental respects: first, we develop a fully decentralized AB-SFC model with several innovative features, and we thoroughly validate it in order to check whether the model is a good candidate for policy analysis applications. Results suggest that the properties of the model match many empirical regularities, ranking among the best performers in the related literature, and that these properties are robust across different parameterizations. Second, the paper has also a methodological purpose in that we try to provide a set or rules and tools to build, calibrate, validate, and display AB-SFC models.